Effect of Propolis on Spermatogenic Cells Number and Diameter of Seminiferous Tubules in Male Mice (Mus musculus) - Nurkarimah, Dona Astari; Hestianah, Eka Pramyrtha; Wahjuni, Retno Sri; Hariadi, Mas’ud; Kuncorojakti, Suryo; Hermadi, Herry Agoes (KnE Life Sciences, 2017)
The present research aimed to determine the effect of propolis in spermatogenic cells number and seminiferous tubules diameter. Group P0 served as control group, P1 (1,6 mg/0,5ml/day), P2 (3,2 mg/0,5 ml/day), P3 (6,4 mg/0,5 ml/day), and P4 (12,8 mg/0,5 ml/day) were given propolis ethanolic extract treatment orally and killed after 14 days. Spermatogenic cells number (spermatogonial cells, primary spermatocytes, spermatids) and seminiferous tubules diameter were observed. The result showed a lower number of spermatogonial in P1 and P2 groups, primary spermatocytes reduction in P2 group, spermatids increased in P1, P3, and P4 group. Seminiferous tubules diameter decreased in P2 and P3 group. P2 group (3,2 mg/0,5 ml/day) showed the lowest result in all parameters (p<0.05). However, oral administration of propolis at these dose for 14 days may decrease spermatogonial cells and primary spermatocytes and increase spermatids number in adult mice. Keywords: Propolis; seminiferous tubule; spermatogenic cells; testis histology